Deltamethrin Residues in Milk and Cheese of Lactating Goats (Capra hircus) - Raffaele Marrone; Abilasha Ramkumar; Giorgio Smaldone; Domenico Rufrano; Claudia Chirollo; Vincenzo Veneziano; Martin Danaher; Aniello Anastasio (Molecules, 2019)
The distribution of pyrethroid insecticide deltamethrin (DLM) in goat milk and cheese (caciotta) following pour-on administration at the sheep dosage (DLMS-10 mL/60 kg body weight) and double dosage (DLMD-20 mL/60 kg body weight) was studied. DLM concentrations were measured in milk collected from study animals (No.14) before treatment and at 2, 4, 8, 12, 16, 24, 30, 36, 48, 56, until 168 h (7 days) post treatment and in caciotta cheese at 12 and 24 h post treatment. At both dosages, the maximum level of DLM residues in goat milk and cheese was below the maximum residue limit (MRL) of 20 μg kg−1 established for bovine milk (EU No 37/2010) at all time points. However, in terms of public health, higher DLM residues in cheese show that further specific studies should be performed on double dosage efficacy and pharmacokinetic and pharmacodynamics properties of ectoparasites in lactating goats.